Integration of Blockchain-Enabled Smart Contracts in Construction: SWOT Framework and Social Network Analysis - Monica Ghaly; Emad Elbeltagi; Adel Elsmadony; Mohamed A. Tantawy (Salehan Institute of Higher Education, 2024)
The construction sector, one of the most ancient industries globally, holds a crucial role in the progress and development of societies. However, it faces persistent productivity and efficiency challenges, rendering it a relative setback when compared to other sectors. In the ever-evolving landscape of the construction industry, characterized by complex projects, numerous stakeholders, and intricate contractual agreements, the integration of emerging technologies presents an unprecedented opportunity for transformation. Smart contracts (SCs), underpinned by blockchain (BC) technology, hold the potential to streamline and revolutionize traditional construction processes. Current literature shows a lack of comprehensive quantitative understanding of how Blockchain-enabled Smart Contracts (BSC) can affect the construction sector. To address this gap, the authors have (1) conducted a systematic keyword analysis of literature on SC in construction from Scopus and Web of Science (WoS) databases; (2) conducted a strengths–weaknesses–opportunities–threats (SWOT) analysis of BSC’s adoption in the construction industry from 174 peer-reviewed papers; (3) identified a holistic list of 72 factors steering BSC adoption in construction, categorized into the 4 aspects of the SWOT framework; (4) performed social network analysis (SNA) to quantitively assess the literature in terms of the identified factors; and (5) conducted clustering analysis to categorize combination of factors frequently highlighted in research publications into common groups. This research offers a comprehensive and methodical evaluation of the potential advantages, applications, and challenges associated with integrating BSC in the construction industry. The findings of SNA and clustering reveal a notable lack of investigation into certain combinations of factors in existing academic research. This disparity and the ensuing knowledge gaps may affect SC’s adoption in the construction sector. To this end, this study equips stakeholders with the insights necessary to make informed decisions in this rapidly evolving sector and contributes to a roadmap for future BSC construction-related research. Doi: 10.28991/CEJ-2024-010-05-020 Full Text: PDF